Epidemiology of overall and early‐onset serrated polyps versus conventional adenomas in a colonoscopy screening cohort. Issue 6 (12th October 2022) - Vithayathil, Mathew; Smith, Scott; Song, Mingyang
Abstract: Serrated polyps (SPs) are precursors to one‐third of colorectal cancers (CRCs), with histological subtypes: hyperplastic polyps (HPs), sessile serrated lesions (SSLs) and traditional serrated adenomas (TSAs). The incidence of early‐onset CRC before the age of 50 is increasing, with limited understanding of SPs in younger cohorts. Using a large colonoscopy‐based cohort, we characterized epidemiologic profiles of SP subtypes, compared to conventional adenomas, with secondary analysis on early‐onset polyps. Ninety‐four thousand four hundred and twenty‐seven patients underwent screening colonoscopies between 2010 and 2018. Demographic, endoscopic and histopathologic characteristics of each polyp subtype were described. High‐risk polyps included SSLs ≥10 mm/with dysplasia and conventional adenomas ≥10 mm/with tubulovillous/villous histology/high‐grade dysplasia. We examined polyp prevalence with age and compared early‐ (age < 50) and late‐onset polyps (age ≥ 50). Eighteen thousand one hundred and twenty‐five patients had SPs (4357 SSLs, 15 415 HPs, 120 TSAs) and 26 699 had conventional adenomas. High‐risk SSLs were enriched in the ascending colon (44.1% vs 2.6‐35.8% for other locations; P < .003). Early‐ and late‐onset SPs had similar subsite distribution. Early‐onset conventional adenomas were more enriched in the distal colon/rectum (51.8% vs 43.4%, P < .001). Multiple conventional adenomas were more represented in late‐onset groups (40.8% vs 33.8%, P < .001), with no difference in SSLs. The prevalence of conventional adenomas/high‐risk conventional adenomas increased continuously with age, whereas the prevalence of SSLs/high‐risk SSLs was stable from age 40 years onwards. A higher proportion of women were diagnosed with early‐onset than late‐onset SSLs (62.9% vs 57.6%, P = .03). Conventional adenomas, SSLs, early‐ and late‐onset polyps have distinct epidemiology. The findings have implications for improved colonoscopy screening and surveillance and understanding the etiologic heterogeneity of CRC. Abstract : What's new? Precursor lesions to colorectal cancer (CRC) include serrated polyps (SPs), which account for nearly one‐third of colorectal malignancies. Nonetheless, epidemiological understanding and characterization of distinct SP subtypes remains limited. In our study, using data from the Partners Colonoscopy Cohort, the authors investigated demographic, endoscopic and histological features of SP subtypes. High‐risk sessile serrated lesions were found to be more common in women, in whom early‐onset lesions were more frequent, and to be highly enriched in the ascending colon. Prevalence of high‐risk sessile serrated lesions stabilized after age 40. The findings highlight the need for high‐quality screening colonoscopy in young adults.